Is there a bilingual advantage: testing the role of language mode - Knyshev, Elena A. (Kansas State University, 2018)
Bilingualism refers to an ability to speak two or more languages and the daily experience involved in coordinating these two languages can have a strong effect on bilinguals’ cognition. For decades, research strongly supported the idea of bilingual advantage; however, recent studies have found no bilingual advantage. Not surprisingly, such conflicting findings raised concerns about the validity of previous research as well as several other methodological issues. For instance, simple cognitive tasks like the Simon task are commonly used in bilingualism research, but they may not best capture bilinguals’ daily experience using the two languages. Bilinguals are constantly suppressing one language while engaged in other tasks, which is better captured by complex working memory (WM) tasks. Most importantly, previous work has not empirically evaluated the effects of language mode on bilinguals’ cognitive performance. Language mode refers to the state of activation of each language. Bilinguals may be in monolingual mode if only one of their languages is activated, whereas they may be in bilingual mode if both of their languages are activated. Previous work has proposed that language mode can have an effect on performance. Thus, the main objective of this dissertation was to evaluate the possible effects of bilingualism on complex WM performance while controlling for language mode and various demographic variables. The Pretest provided initial evidence that language mode affected performance on a simple cognitive task like MPWI. Therefore, a similar language mode manipulation was used in the Main study while testing performance on several complex WM tasks (CSPAN, OSPAN, and RotSpan) and the Simon task for monolinguals, bilinguals in bilingual mode, and bilinguals in monolingual mode. No significant differences were observed between all bilinguals and all monolinguals on any of the measures. However, significant differences were observed once language mode was accounted for. That is, bilingual participants in bilingual mode outperformed both bilingual participants in monolingual mode and monolingual participants on measures of complex WM. Further, there were no differences between monolinguals and bilinguals in monolingual mode. Thus, being in monolingual mode and fully suppressing one language may require more inhibition resources than bilingual mode in which both languages are active, and as a result, there may be fewer resources left to complete the complex WM span tasks. Importantly, the current work shed light on the hotly debated issue of the existence of a bilingual advantage by identifying a third variable that may explain the conflicting results in the literature. That is, no bilingual advantage was observed, but the current data provide evidence of a bilingual mode advantage.
Keywords: bilingualism; language mode; working memory; bilingual advantage; language fluency; language proficiency